2014
DOI: 10.7224/1537-2073.2013-017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Symptom Recrudescence at the End of the Natalizumab Dosing Cycle

Abstract: Background: This study was undertaken to determine how frequently patients receiving natalizumab for multiple sclerosis (MS) experience recrudescence of their MS symptoms at the end of the dosing cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
0
19
2
2
Order By: Relevance
“…Studies that do address this phenomenon report an incidence of the wearing-off effect of 61%-67%. [3][4][5] The incidence in our cohort is slightly lower (54%) and we show that the majority of these patients do not experience the wearing-off effect during every cycle. In earlier work, we have shown that intraindividual trough natalizumab concentrations are stable in a set infusion interval.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Studies that do address this phenomenon report an incidence of the wearing-off effect of 61%-67%. [3][4][5] The incidence in our cohort is slightly lower (54%) and we show that the majority of these patients do not experience the wearing-off effect during every cycle. In earlier work, we have shown that intraindividual trough natalizumab concentrations are stable in a set infusion interval.…”
Section: Discussionmentioning
confidence: 70%
“…By far the most reported wearing-off symptom was fatigue, which is in agreement with other reports. [3][4][5] Natalizumab led to significant improvement of fatigue symptoms after 1 year of treatment in a one-arm, open-label trial. 18 However, in one of the pivotal trials, fatigue was reported significantly more frequently as an adverse event in the natalizumab group than in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies. Depression was reported most often (n = 4, IPs 0.1-12%) (Butzkueven et al, 2014;Horga et al, 2011;Penner et al, 2015;Ratchford et al, 2014), followed by anxiety/panic attack (3 Fig. 2.…”
Section: Study Characteristicsmentioning
confidence: 98%
“…Ten studies (8 observational studies, 2 RCTs) examined changes in depression symptoms following Natalizumab treatment (Iaffaldano et al, 2012;Kunkel et al, 2015;Lang et al, 2012;Nagesh et al, 2015;Penner et al, 2015;Ratchford et al, 2014;Rorsman et al, 2017;Rudick et al, 2006;Sater et al, 2016;Svenningsson et al, 2013); only 5 provided the information needed for meta-analysis. The meta-analysis of these studies (Kunkel et al, 2015;Lang et al, 2012;Ratchford et al, 2014;Rorsman et al, 2017;Sater et al, 2016), found that depression symptoms improved (Fig. 4C, SMD: 0.31 [−0.06; 0.68]), although this was not statistically significant.…”
Section: Natalizumabmentioning
confidence: 99%